OP0102 Prolonged image acquisition time after contrast agent administration results in increased synovial thickness on post-contrast mri of jia patients: standardisation is key. (12th June 2018) - Barendregt, A.M.; van Gulik, C.; Groot, P.; Dolman, K.; van den Berg, M.; Rashid, A. Nassar Sheikh; Schonenberg-Meinema, D.; Lavini, C.; Rosendahl, K.; Hemke, R.; Kuijpers, T.W.; Maas, M.; et al.
Abstract : Background: Timing of acquisition of post-contrast MR images for the assessment of the synovial membrane is important: delayed acquisition can result in contrast washout into synovial fluid. 1 Several authors demonstrated the importance of this timing using qualitative data (membrane appearance on MRI). 1–4 Nonetheless, there is no international consensus on timing of post-contrast images in arthritis, leading to acquisitions at 1 to 10 min after contrast injection. 1 5 This could result in incorrect measurement of synovial thickness and thus imprecise assessment of disease activity and over or under treatment of patients. Objectives: To quantitatively measure and compare thickness of the synovial membrane on early and late post-contrast knee MRI in patients with juvenile idiopathic arthritis (JIA). Methods: Prospectively collected dynamic contrast-enhanced T1 MRIs of children with JIA were used to measure synovial thickness at time point 1 (TP1), 1 min and TP2, 5 min after contrast administration. Written and verbal informed consent for participation in our IRB-approved study was obtained. Two experienced readers, who were blinded for the time point, independently measured synovial thickness on a predefined, marked location in the patellofemoral compartment on randomised images. The Wilcoxon test was used to compare the mean synovial thickness measurements from TP1 and TP2. Moreover, we studied the number of patients judged to have active synovial inflammation (synovium >2 mm) on both time points. Results: Measured synovial thickness in 53 patients with JIA (median age 13.5 years, 58.6% female) increased with prolonged time-after-contrast (TP1 1.4 mm and TP2 1.5 mm, p<0.001). Moreover, we found a 25% relative increase of patients with active synovial inflammation (synovial membrane >2 mm) when comparing the measurements at TP2 versus TP1. Conclusions: Our study is the first to add quantitative data to the literature showing that synovial thickness as measured on post-contrast MRI increases with a prolonged interval between contrast administration and acquisition of the post-contrast images. Our data, together with previous studies 1 3 4 indicate that it is questionable whether one can reliably measure synovial thickness without standardisation of the interval between contrast administration and acquisition of post-contrast sequences. This could not only influence clinical interpretation and quantitative scoring in JIA, but possibly also impacts other rheumatologic diseases in which synovial thickness is quantified in scoring systems, such as rheumatoid arthritis and osteoarthritis. 6 7 References: [1] Østergaard, et al. ARD 2001;60:1050–1054. [2] Kursunoglu, et al. Radiology1990;176(3):831–835. [3] Yamato, et al. J CAT 1993;17(5):781–785. [4] Rieter, et al. Pediatr Radiol2016;46(11):1562–1567. [5] Johnson, et al. Clin Radiol2002;57(6):466–471. [6] Østergaard, et al. J Rheumatol2003;30:1385–1386.1. [7] Guermazi, et al. Ann Rheum Dis2011;70(5):805–811. Disclosure of Interest: None declared